Experience of Using Bluetooth Low Energy to Develop a Sensor Data Exchange System Based on the NRF52832 Microcontroller - Salikhov, R. B.; Abdrakhmanov, V. Kh; Yumalin, T. T. (International Ural Conference on Measurements (Online), 2021)
A brief overview of Bluetooth Low Energy technology is presented: API and built-in data exchange toolkit are considered. The main capabilities of the Bluetooth 5.2 version and the validity of its use in industrial wireless data transmission systems are shown. The idea of creating wireless monitoring systems based on the NRF52832 microcontroller is presented. The technology makes it possible to conveniently implement a data exchange system and includes the necessary tools for its implementation - packet integrity check (CRC), packet delivery check (response), data encryption, automatic retrieval of up-todate data. The experience of development in the Segger Embedded Studio and Xcode environments is shown. The server and client parts of the project have been implemented. Data exchange between devices has been carried out. Considered a development tools for server and client devices. Also in this article, a comparison is made with competing technologies such as ZigBee. In addition, possible industrial applications of the technology were considered.